TECHNOLOGY «BOOK TALK» IN THE WORK OF A PRIMARY TEACHER IN CANADA AND UKRAINE - Khomych, Oksana (Continuing Professional Education: Theory and Practice, 2019)
Under the conditions of the development of the New Ukrainian School, there is a borrowing of international educational experience, which is conditioned by the introduction of high-quality world practices, technologies into the educational process. The article describes the features of the formation and development of «Book Talk» technology for the development of readers’ skills and motivation of elementary school students to read. The possibilities of implementation of effective educational technology in general educational institutions of Ukraine are substantiated. The attention is paid to the history of the development of this technology and its implementation in educational and public cultural institutions (libraries, reading centers, book clubs). The need to explore the technology of «Book Talk» is necessary in order to attract students to reading fiction, analysis of artistic works, conducting discussions, peer interest in reading the book. After all, in the context of the rapid development of the world, one of the main tasks of the New Ukrainian School is the maximum interest of students in the book, making it competitive with the digital world (television, the Internet).